Improving productivity in Kenyan smallholder dairy systems through selective, intensive education and supported adoption - Goopy, John P.; Gakige, J.K. (International Livestock Research Institute, 2016)
Improving productivity in Kenyan smallholder dairy systems is perceived as having the potential to greatly improve the supply of milk to processors and make substantial improvements in rural incomes by doing so. Surveys recently commissioned by GIZ in Western Kenya indicated that milk yield was between 1.8-3L/cow/d (depending on county). Poor milk yield is often attributed to poor genetics, but we discovered that frequently production is constrained by a lack of knowledge, particularly with regard to husbandry, feeds and feeding practice. Much has already been done in these areas by NGOs, but training is frequently short-term, focused on a narrow area and participant selection is untargeted. In the framework of a BMZ funded project we are working with NGOs, dairy co-operatives and GIZ to assess the potential of farmers to implement new technologies that will further improve their operations. We are specifically aiming at early adopters as those are likely to continue and thus, might serve as role models. We are currently identifying innovators in a number of communities in Western Kenya and will provide them with an 18d intensive course covering husbandry, animal nutrition, forage/crop agronomy and business analysis skills. On completion we will support each farmer to implement knowledge and technology in his/her community. These farmers should be able to adapt the skill set and learned technologies to their own situation, but also act as a focal point and exemplar to their own community. The presentation will outline the training concept, selection procedure of farmers, and summarise first results on knowledge implementation in the communities following the return of the trainees.